Sequence and relative timing of large lakes in Gale crater (Mars) after the formation of Mount Sharp. Issue 3 (30th March 2016) - Palucis, Marisa C.; Dietrich, William E.; Williams, Rebecca M. E.; Hayes, Alexander G.; Parker, Tim; Sumner, Dawn Y.; Mangold, Nicolas; Lewis, Kevin; Newsom, Horton
Abstract: The quantification of lake levels in Gale crater is important to define the hydrologic and climatic history experienced by the sedimentary deposits found by Curiosity . We propose that there were at least three major lake stands within Gale, each persisted >1000 years, and all occurred after Mount Sharp reached close to its current topographic form. Deltaic deposits off the southern rim of Gale, derived from incision of Farah Vallis, and corresponding deposits off the southern flank of Mount Sharp define the highest lake level, which had a mean depth of 700 m. Canyons similar in form to Farah Vallis enter into craters and/or the crustal dichotomy near Gale from the south, suggesting that the highest lake was supplied by a large‐scale flow system. The next lake level, established after a period of drying and rewetting, is defined by four deltaic features, three sourced from Mount Sharp and one from the western rim of Gale, as well as the termination of gullies around the northern rim of Gale. This second lake level had a mean depth of 300 m. The presence of the gullies suggests more locally sourced water. Lake levels then rose another 100 m, as evidenced by two deltaic deposits derived from the rim of Gale and the termination of a second set of gullies. Post‐lake, reduced hydrologic activity continued, evidenced by a time of fan building (including Peace Vallis). The sequence of events suggests an episodic shift through time from relatively wet regional conditions to a drier environment with local runoff. Key Points: Delta deposits within Gale suggest a series of lake stands post‐Mount Sharp development Incisional and depositional processes record a sequence of falling then rising lake levels Water supply for lakes likely shifted from a regional to more local source over time